PENGARUH MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI DI SEKOLAH DASAR - Veronica, Elda; Halidjah, Siti; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this research is "How is the effect of using the serial image to the writing skill description in class III State Elementary School 35 South Pontianak?". This study aims to analyze the effect of the use of serial images on the skill of writing descriptions in class III State Elementary School 35 Pontianak Selatan. This research uses experimental method, with Quasi Experimental Design form. Population and sample in this research is all student of class III State Elementary School 35 Pontianak Selatan which amounts to 65 people. Techniques used in data collection is a measurement technique with the tool used is essay-shaped written test and documentary / bibliographic study technique that is collecting photographs of research conducted. Based on the data analysis, the average of the result of the final test (post-test) of the experimental class is 80,91 and the mean of the final test result (post-test) of control class student is 75,72. After t test is obtained t count of 2.0513 while ttable (= 5% of 1.6749, it turns thitung ≥ ttable or 2.0513 ≥ 1.6749 which means there is a significant effect on the use of serial image media From the calculation of effect size obtained by 0.388 with criteria classified moderate.This means the use of media drawing series to give a moderate effect on the skill of writing a description in the class III State Elementary School 35 Pontianak Selatan. Keywords: Influence, Media Image Series, Essay Description.